2007
DOI: 10.1007/s00270-007-9090-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Renal Tumors by Image-Guided Radiofrequency Ablation: Experience in 105 Tumors

Abstract: Aims In this article we present our experience with radiofrequency ablation (RFA) in the treatment of 105 renal tumors. Materials and Methods RFA was performed on 105 renal tumors in 97 patients, with a mean tumor size of 32 mm (11-68 mm). The mean patient age was 71.7 years (range, 36-89 years). The ablations were carried out under ultrasound (n = 43) or CT (n = 62) guidance. Imaging followup was by contrast-enhanced CT within 10 days and then at 6-monthly intervals. Multivariate analysis was performed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(71 citation statements)
references
References 23 publications
10
59
0
2
Order By: Relevance
“…After the application of a second RFA in this case, the subsequent first month control showed no enhancing, viable, residual tumor. Therefore, the overall success rate was accepted as 100%, which was comparable to the previous literature (Arima et al, 2007;Breen et al, 2007;Mylona et al, 2009;Salas et al, 2010;Altunrende et al, 2011;Iannuccilli et al, 2012;. The presence of incomplete ablation at initial RFA only in USG-PRFA application was supposed that the preferred technique could influence the RFA results.…”
Section: Resultssupporting
confidence: 68%
“…After the application of a second RFA in this case, the subsequent first month control showed no enhancing, viable, residual tumor. Therefore, the overall success rate was accepted as 100%, which was comparable to the previous literature (Arima et al, 2007;Breen et al, 2007;Mylona et al, 2009;Salas et al, 2010;Altunrende et al, 2011;Iannuccilli et al, 2012;. The presence of incomplete ablation at initial RFA only in USG-PRFA application was supposed that the preferred technique could influence the RFA results.…”
Section: Resultssupporting
confidence: 68%
“…In view of these factors, and because current evidence is based mainly on single-centre series and a few meta-analyses, there is uncertainty about the best treatment of SRMs. [9][10][11][12] Minimally invasive ablation SRMs (of < 4 cm in size) clearly make available a new treatment option, but robust data comparing relative clinical effectiveness and cost-effectiveness of active surveillance with ablative techniques (RFA/CRYO) are currently not available. A randomised controlled trial (RCT) to answer this question has been identified as a priority by the renal cancer subgroup of the National Cancer Research Institute (NCRI) and has the support of the British Association of Urological Surgeons (BAUS) section of oncology and local National Institute for Health Research (NIHR) clinical research networks.…”
Section: Fundingmentioning
confidence: 99%
“…RFA [31][32][33][34][35][36][37][38][39][40][41] ) that met all inclusion criteria and were included in the meta-analysis of case series studies.…”
Section: Absence Of Rcts On Ca Compared To Rfa For Renal Cell Carcinomamentioning
confidence: 99%